Desenvolvimento de um data logger aplicado ao monitoramento de encostas - Vargas, Mauricio Tonello (2016)
The existence of slopes in the environment, whether natural or artificial, emphasizes the importance of studies to identify, improve their use, as well as to prevent the movement of masses of soil that can damage both nature and the population. Therefore, this study aimed to address the construction of a low cost system applied to the monitoring (in situ and in distance) of geotechnical works. The information acquired by this system is vital to the management of risk areas, and to support monitoring of slopes, tunnels, retaining structures and others. Hence, the study focused on the use of electronic components inserted into incased probes on slopes prone to landslides. The technologies applied to the inclination sensor derived from electromechanical systems (MEMS) that convert a mechanical movement into an electronic signal, which must be interpreted in order to generate a magnitude that enables the assessment of the slope. The collected data must be transmitted by the probe digitally for the developed Data Logger, which will carry out the transcription of the received data in an organized way for later archiving in standard *.CSV, commonly used for data files that can later be viewed by a spreadsheet program like Excel®.